1996
DOI: 10.1007/bf00196651
|View full text |Cite
|
Sign up to set email alerts
|

Developing tomato seeds when removed from the fruit produce multiple forms of germinative and post-germinative endo-?-mannanase. Responses to desiccation, abscisic acid and osmoticum

Abstract: Abstract. Several isoforms of endo-l,413-D-mannanase (EC3.2.1.78) are produced in the endosperm and embryo of tomato (Lycopersicon esculentum Mill.) seed prior to the completion of germination. Other isoforms appear in the embryo and in the lateral endosperm following germination. This occurs in seeds removed from the fruit prior to completion of development at 45 d after pollination and placed directly on water, or following drying. Hence desiccation is not required to induce either germination-or post-germin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…This observation must be reconciled with the multiple (1®4)-b-mannanase isoforms that have been separated from extracts of germinated tomato seed by isoelectric focussing, where up to 15 active (1®4)-b-mannanase bands are visible (Fig. 4) (Toorop et al 1996;Voigt and Bewley 1996). The obvious conclusion is that many of the isoforms present on isoelectric focussing gels are not true genetic isoenzymes, but are generated from a relatively small number of (1®4)-b-mannanases by post-translational modi®cations.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This observation must be reconciled with the multiple (1®4)-b-mannanase isoforms that have been separated from extracts of germinated tomato seed by isoelectric focussing, where up to 15 active (1®4)-b-mannanase bands are visible (Fig. 4) (Toorop et al 1996;Voigt and Bewley 1996). The obvious conclusion is that many of the isoforms present on isoelectric focussing gels are not true genetic isoenzymes, but are generated from a relatively small number of (1®4)-b-mannanases by post-translational modi®cations.…”
Section: Discussionmentioning
confidence: 94%
“…This can be compared with a value of 38 000 reported for the (1®4)-b-mannanase isoform MI puri®ed from tomato endosperm (Nonogaki and Morohashi 1996). The pI calculated from the primary structure of the enzyme is 5.3; isoelectric focussing of endosperm extracts from germinated tomato seeds revealed the presence of several isoforms with pI values in the range 5.2±5.8 (Toorop et al 1996;Voigt and Bewley 1996).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Three enzymes contribute to the hydrolysis of the galactomannans: ␣-galactosidase, a mannohydrolase, and endo-␤-mannanase. More recent studies (focusing on endo-␤-mannanase) have revealed that only the isoforms of the enzyme that are produced during germination have a potential role in weakening the endosperm (Nonogaki and Morohashi, 1996;Toorop et al, 1996;Voigt and Bewley, 1996). Endo-␤-mannanase is also produced in the endosperm of lettuce seeds when the seeds are released from dormancy by GA or red light (Halmer et al, 1976) and seeds of Datura ferox produce endo-␤-mannanase and ␤-mannosidase in the micropylar region of the endosperm after red-light stimulation, several hours before the radicle protrudes through it (Sanchez and de Miguel, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The physical weakening of the endosperm cap tissue to allow radicle emergence is dependent upon gibberellin (GA) (Groot and Karssen, 1987). Endosperm cap weakening is accompanied by an increase in the activity of cell wall hydrolytic enzymes, including endo-␤-mannanase (Groot et al, 1988;Nomaguchi et al, 1995;Nonogaki and Morohashi, 1996;Voigt and Bewley, 1996;Dahal et al, 1997;Nonogaki et al, 1998), cellulase (Sánchez et al, 1985;Leviatov et al, 1995), polygalacturonase (Sitrit et al, 1999), arabinosidase, ␤-1,3-glucanase, and chitinase (Bradford et al, 2000). In addition, the loss of lipid and protein bodies and cellular vacuolization occurs initially in the radicle tip and endosperm cap tissues prior to radicle emergence (Mella et al, 1995;Nonogaki et al, 1998).…”
mentioning
confidence: 99%